PENDEKATAN ARSITEKTUR PRILAKU PADA PERMUKIMAN PELABUHAN TANJUNG DI KABUPATEN TOLITOLI - Saputra, Andika; Pahude, Mansur S.; Rosid, Mohammad (Architecture Study Program, Faculty of Engineering, Madako University Tolitoli, 2024)
Population growth in Indonesia that continues to increase every year has a direct consequence on the increasing need for space, both for housing, public facilities, and infrastructure. With a population projected to reach more than 300 million in the next few decades, the challenges faced are not only limited to providing housing, but also meeting the socio-economic needs of the community such as education, health, transportation, and green open spaces. The purpose of this study is to solve the problem of population density in the Tanjung Port settlement so that it can create a more decent, healthy, and orderly residential environment for the fishing community living in the area. This study uses a qualitative method. Data were collected through interviews, questionnaires, and field studies, which were then analyzed using data display techniques, grouping, reduction, and data interpretation. The concept of behavioral architecture is applied as a responsive approach to understanding the interaction between humans and their environment. The results of the study indicate that the concept of behavioral architecture in overcoming the problem of population density can be done with several important findings. First, the rearrangement of residential space that is more efficient and flexible, allows for optimal land use without sacrificing the comfort of residents. Second, the integration of multifunctional public spaces, such as green areas and shared facilities, can increase social interaction and reduce pressure on private space. Third, the use of adaptive design that is responsive to the daily habits and behaviors of residents, helps create a more harmonious and productive environment. The findings also emphasize the importance of collaboration between architectural elements and human behavior to create holistic and sustainable solutions.